From Turtle Island to Gaza - Groulx, David (Athabasca University Press, 2021)
With a sure voice, Groulx, an Anishnaabe writer, artistically weaves together the experiences of Indigenous peoples in settler Canada with those of the people of Palestine, revealing a shared understanding of colonial pasts and presents. Published